Dust Concentration in Air during the MDF Boards and Polystyrene Milling Operations on CNC Milling Machine - Kic, Pavel; Muller, Miroslav (Manufacturing Technology Journal, 2018)
During the material milling an amount of dust which can significantly influence surroundings is generated. Mainly workers are exposed to a dust pollution. The aim of this paper is to present results of a microclimatic research focused on the dust pollution in a workshop during the milling of MDF boards (Medium Density Fibreboards) and Polystyrene workpieces on CNC milling machine. The concentration of air dust was measured by the DustTRAK II Model 8530 aerosol monitor. Using the special impactors the PM1, PM2.5, PM4, PM10 size fractions were also measured. Obtained results of measurements and concentrations of different size of dust particles were analysed. The conclusion of the research is that it is necessary to watch the optimization of the milling process as well as secondary effects of the technological operations and the inner environment of workshops which can be contaminated by dust particles. A natural ventilation of the large space in which the CNC milling machine is installed is not sufficient. A recommendable solution for an improvement of the current situation is the installation of a local exhausting equipment.
Keywords: Dust fractions; Manipulation; Natural ventilation; Workshop